Disseminated M. bovis Infection and Vertebral Osteomyelitis following Immunotherapy for Bladder Cancer - Harpreet S. Gill; Suhas P. Dasari; Sarbagya Pandit; Thomas E. Ritter; Sushma B. Raju; Alexander R. Chartier; Pinky Jha (Case Reports in Infectious Diseases)
The use of BCG in immunotherapy for bladder cancer has been in practice for over 40 years. However, uncommon, serious complications can occur with the therapy. Here, we present a case of vertebral osteomyelitis secondary to dissemination of BCG following immunotherapy, an exceedingly rare presentation of an already rare complication.